Faktor – faktor yang Mempengaruhi Penerimaan Diri Pasien dengan Gagal Ginjal Kronik yang Menjalani Terapi Hemodialisis - Kuwa, Maria Kornelia Ringgi; Wela, Yustina; Sulastien, Herni (Jurnal Keperawatan Jiwa (JKJ): Persatuan Perawat Nasional Indonesia, 2022)
A healthy human being is a key factor in the success of a national development. The implementation of health development includes health efforts and resources that must be carried out in an integrated and sustainable manner in order to achieve optimal and comprehensive results so that the Government of the Republic of Indonesia triggers the Healthy Indonesia 2025 movement. Efforts to achieve the vision and mission of Healthy Indonesia 2025 are still experiencing various obstacles. This is because there are still high problems of degenerative diseases, namely diseases that arise because of to the process of declining body cell function from normal to bad conditions. One of these degenerative diseases is Chronic Kidney Disease (CKD). The sufferer feels that he cannot be independent so he thinks that he is only a bother to others. In addition, the sufferer also feels that he has nothing to be proud of. If this condition lasts for a long period of time without any special intervention, then they will have difficulty accepting themselves. The type of this research used is descriptive quantitative method by describing the factors that influence the self-acceptance of patients with Chronic Kidney Failure undergoing dialysis therapy in Maumere, Sikka Regency. The population in this study were all patients with chronic kidney failure who underwent dialysis therapy at dr. T. C. Hillers as many as 70 patients. The sampling technique used was total sampling involving all patients undergoing hemodialysis therapy. The researcher used univariate analysis to find out the frequency distribution of the respondent's characteristics.